The Politics of Exile: Ama Ata Aidoo's Our Sister Killjoy - Gay Wilentz (Studies in 20th & 21st Century Literature, 1991)
Ama Ata Aidoo's Our Sister Killjoy or Reflections from a Black-Eyed Squint is a relentless attack on the notions of exile as relief from the societal constraints of national development and freedom to live in a cultural environment conducive to creativity. In this personalized prose/poem, Aidoo questions certain prescribed theories of exile (including the reasons for exile)—particularly among African men. The novel exposes a rarely heard viewpoint in literature in English—that of the African woman exile. Aidoo's protagonist Sissie, as the "eye" of her people, is a sojourner in the "civilized" world of the colonizers. In this article, I examine Aidoo's challenge to prevailing theories of exile, her questioning of the supposed superiority of European culture for the colonial subject, and her exposé of the politics of exile for African self-exile. Through a combination of prose, poetry, oral voicing and letter writing, Aidoo's Sissie reports back to her home community what she sees in the land of the colonizers and confronts those exiles who have forgotten their duty to their native land.
Keywords: Ama Ata Aidoo; Our Sister Killjoy or Reflections from a Black-Eyed Squint; exile; societal constraints; freedom; creativity; community; society; personalized prose/poem; prose; poem; theories of exile; African men; literature; English; African woman exile; African woman; Sissie; eye; sojourner; civilized; colonizer; colonizers; superiority; European culture; colonial subject; exposé; Africa; African; self-exile; poetry; oral voicing; letter writing; native land; duty